Extracellular Mitochondria in Traumatic Brain Injury Induced Coagulopathy - Zhao, Zilong; Zhou, Yuan; Li, Min; Zhang, Jianning; Dong, Jing-Fei (Seminars in Thrombosis and Hemostasis, 2020)
Traumatic brain injury (TBI) induced coagulopathy remains a significant clinical challenge, with unmet needs for standardizing diagnosis and optimizing treatments. TBI-induced coagulopathy is closely associated with poor outcomes in affected patients. Recent studies have demonstrated that TBI induces coagulopathy, which is mechanistically distinct from the deficient and dilutional coagulopathy found in patients with injuries to the body/limbs and hemorrhagic shock. Multiple causal and disseminating factors have been identified to cause TBI-induced coagulopathy. Among these are extracellular mitochondria (exMTs) released from injured cerebral cells, endothelial cells, and platelets. These circulating exMTs not only express potent procoagulant activity but also promote inflammation, and could remain metabolically active to become a major source of oxidative stress. They activate platelets and endothelial cells to propagate TBI-induced coagulopathy and secondary tissue injury after primary traumatic impact. In this review, we discuss recent advances in our understanding of the role of exMTs in the development of TBI-induced coagulopathy.
Keywords: traumatic brain injury; mitochondria; extracellular vesicle; coagulopathy; inflammation